Sienkiewicza przygody z literaturą „trzecią” - Szargot, Barbara (Wydawnictwo Uniwersytetu Rzeszowskiego, 2016)
The article is a review of the book by Agnieszka Kuniczuk-Trzcinowicz, "Sienkiewicza talent i intuicja. Studia i szkice" ["Talent and Intuition of Sienkiewicz. Studies and Sketches"], published in Opole in 2014. The publication is an interesting example of analysis of relations between popular literary conventions and the works by Sienkiewicz. According to the reviewer, the essential merit of the book is the ambitious comparative idea – conventions of popular literature are observed not only in the novels by Henryk Sienkiewicz, but also in other 19th century works that belong to the canon of high literature.
Sienkiewicz’s Adventures with “Third-Rate” Literature
Keywords: Henryk Sienkiewicz; historia literatury polskiej; pozytywizm; literatura popularna; konwencja literacka; history of Polish literature; Positivism; popular literature; literary convention